UPAYA MENINGKATKAN KUALITAS PEMBELAJARAN KINEMATIKA DAN DINAMIKA MESIN MELALUI IMPLEMENTASI LEMBAR KERJA TERSTRUKTUR DI JURUSAN PENDIDIKAN TEKNIK MESIN - Asnawi Asnawi; Paryanto Paryanto (Faculty of Engineering, Universitas Negeri Yogyakarta, 2012)
ABSTRACTThe purpose of this study is to improve the learning quality of Kinematics and Dynamic of Mechanical System course through a structural worksheet. The improvement in this context referes to students’activities and their learning motivation. This reserach was conducted by using action reserach method on Kinematics and Dynamic of Mechanical System course in odd semester. The reserach object was the third semester students of Information Technology Department. Data collection techniques were observation, decumentation, and interview. Data analysis technique was using descriptive analysis which was presented in the form of quantitaive.The result of the reserach showed that 1) the implementation of structural worksheet was able to improve the students’learning activities on Kinematics and Dynamic of Mechanical System course (20%), 2) the implementation of structural worksheet was able to improve the students’learning motivation (40%).Keywords : learning activities, learning achievement and structural worksheet